Exploring the conformational landscape of menthol, menthone, and isomenthone: a microwave study - Schmitz, David; Shubert, V. Alvin; Betz, Thomas; Schnell, Melanie (Frontiers in Chemistry, 2015)
The rotational spectra of the monoterpenoids menthol, menthone, and isomenthone are reported in the frequency range of 2–8.5 GHz, obtained with broadband Fourier-transform microwave spectroscopy. For menthol only one conformation was identified under the cold conditions of the molecular jet, whereas three conformations were observed for menthone and one for isomenthone. The conformational space of the different molecules was extensively studied using quantum chemical calculations, and the results were compared with molecular parameters obtained by the measurements. Finally, a computer program is presented, which automatically identifies different species in a dense broadband microwave spectrum using calculated ab initio rotational constants as initial input parameters.